IT GOVERNANCE DESIGN IN IMPROVING THE QUALITY OF DATA AND INFORMATION SECURITY USING COBIT 2019 - Setya, Bagus; Muhammad, Alva Hendi; Kurniawan, Mei Parwanto (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This study aims to enhance the quality of data and information security at PT XYZ by developing Information Technology (I.T.) governance based on the C.O.B.I.T. 2019 framework. Data and information security are of utmost importance for Business Continuity in the contemporary digital age, particularly for companies operating in the property development industry, such as PT XYZ. The selection of C.O.B.I.T. 2019 as the framework is based on its comprehensive approach to I.T. governance, encompassing areas such as planning and organizing, acquisition and implementation, delivery and support, and monitoring and evaluation. The objective of this research is to pinpoint deficiencies in existing I.T. governance procedures and provide suggestions for improved measures that may be implemented to strengthen data and information security. The study entails qualitative analysis conducted through comprehensive interviews with essential stakeholders and examination of pertinent documents. An action plan is established based on the findings, which entails deploying an I.T. governance team and formulating more stringent security standards. By implementing the I.T. governance plan derived from C.O.B.I.T. 2019, PT XYZ aims to enhance the quality of data and information security, thus bolstering the company’s long-term viability and expansion